Congressional Debates Over Prisoner Education: A Critical Discourse Analysis - Yates, Mark Timothy (2009)
The United States has the highest incarceration rate of any country. The causes for the large number of prisoners can be traced, in part, to a politicized war on crime that resulted in harsh sentencing and high recidivism rates. Prisoner education provides the potential for slowing the revolving door of prison by helping to create engaged citizens, who are committed to bettering themselves and their communities. However, there is a paucity of support for programs such as Pell Grants, which could facilitate emancipatory education in prisons. The purpose of this work is to examine why prisoners are provided few meaningful educational opportunities while incarcerated. This study seeks to understand the genealogy of prisoner education policy through an examination of the debate surrounding the 1994 Omnibus Crime Bill and its prohibition of Pell Grants for prisoners, as well as the 2008 Second Chance Act and its reentry programs. The study analyzes the ideological underpinnings of key decision makers and how their values are often embedded in the narratives of neoliberalism. In addition, the work examines elite stakeholders’ discursive attempts, both manifest and subtle, to influence and maintain social policy through the creation of legitimizing myths, including the viewpoints that prisoners are hopelessly flawed or that they have potential only as human capital. Counter-hegemonic discourse is also described. The study methods are critical discourse analysis which looks at the ways text and talk maintain inequities in society and critical policy analysis. Utilizing transcripts from legislative debates, the study analyzes the discourses of members of Congress to expose the tropes that often lie beneath the surface of the debate over prisoner education. Their rhetoric appears to generate and maintain widespread support for legislation that is frequently deleterious to marginalized out-groups. The study should add to the literature examining the role of legitimizing myths that maintain inequities in educational access